KNOWLEDGE, ATTITUDE AND PREVALENCE OF EARLY MARRIAGE AMONG ADOLESCENTS IN SASA, AKINYELE LOCAL GOVERNMENT AREA NIGERIA (2013)
The practice of early marriage has persisted in some Nigerian tribes, despite its associated negative health effects. There is however inadequate information on adolescents’ knowledge and attitude towards this practice. This study was therefore conducted to determine knowledge, attitude and the prevalence of early marriage among adolescents in Sasa, a multi-ethnic community in Akinyele Local Government Area Nigeria. Using a three-stage sampling technique, 400 adolescents were recruited into this cross-sectional study. An interviewer-administered questionnaire was used to obtain information on socio-demographic characteristics, knowledge, attitude and prevalence of early marriage. Knowledge of early marriage and associated problems was assessed using a 15-item scale categorized as poor (<8) and good (≥8) knowledge. Attitude to early marriage was assessed with a 17-item 5-point likert scale with minimum and maximum scores of 17 and 85 respectively; scores <51 were categorized as unfavourable and ≥51 as favourable to early marriage. Data were analyzed using descriptive and Chi-square statistics. Sixty-three percent of respondents were male, majority (67.5%) were Yoruba, 26.4% were Hausa and 6.0% comprised other ethnic groups. Overall mean age was 16.1±2.3 years, the mean ages of Yoruba, Hausa and adolescents belonging to other ethnic groups were 16.4±2.0, 15.3±2.6 and 15.3±2.4 years respectively. Sixty-one percent of respondents had secondary education. Seventy-four percent of respondents had good knowledge of early marriage and associated problems. Common associated problems mentioned were deprivation of childhood (76.8%), poor child care (75.8%), obstructed labour (68.3%), high risk of vessico-vagina fistula (65.2%), poor access to contraceptives (65.2%) and high risk of HIV/AIDS (59.4%). Fifty-nine percent of respondents were not favourably disposed to early marriage. Seventy-percent of respondents reported that early marriage was a common practice in their community. Common reasons for the practice were prevention of premarital sex (88.8%), teenage pregnancy (82.7%), poverty (77.9%) and upholding tradition (72.8%). Of 23 (16%) female respondents who were currently married, 52.2% were Hausa, 39.1% were Yoruba and 8.7% were from other ethnic groups. About 74% of those currently married did so before 18 years and the majority (73.9%) of these were Muslims. The mean age at marriage was 15.7±1.9 years. The mean age at marriage for Yoruba was 16.9±1.3, Hausa (15.0±2.0) and other ethnic groups (15.5±0.7). A higher proportion of 15-19 years (78.0%) than 10-14years (59.3%) adolescents had good knowledge of early marriage and associated problems (p<0.05). Also, more 10-14 years (69.2%) than 15-19 years (32.8%) adolescents had favourable attitude to early marriage (p<0.05). Religious practice was significantly associated with early marriage with more Muslims (52.9%) than Christians (29.0%) favourably disposed to the practice (p<0.05). A higher proportion of Hausa (52.4%) than Yoruba (34.2%) had favourable attitude to early marriage (p<0.05). Adolescents in the study area have good knowledge about early marriage and its associated problems. However their attitude towards the practice was influenced by age, religion and ethnicity. Religious and cultural sensitisation of adolescents, their parents and community can help reduce this practice.